Quantitative Optimization of Workpiece-fixture System's Clamping Forces - Lu Jiping; Zuo Jianhua; Ma Ning; Zhang Faping; Qian Hanbo (International Journal of Computational Intelligence Systems, 2011)
The paper discusses the stability of workpiece-fixture system and quantitative optimization of clamping forces during precise machining. Based on the force screw theory and the minimum norm principle, a mathematical model is formulated to calculate the entire passive forces acting on the workpiece. Furthermore, a new methodology to optimizing clamping forces is put forward, on the criteria of keeping the stability of workpiece during cutting process. By this way, the intensity of clamping forces is decreased dramatically, which is the most beneficial in improving machining quality of thin-walled machined parts. Finally, a case study is made to support and validate the proposed model.